Hydrogen Blending in Gas Pipeline Networks—A Review - Mahajan, Devinder; Tan, Kun; Venkatesh, T.; Kileti, Pradheep; Clayton, Clive R. (Energies (Basel), 2022)
Replacing fossil fuels with non-carbon fuels is an important step towards reaching the ultimate goal of carbon neutrality. Instead of moving directly from the current natural gas energy systems to pure hydrogen, an incremental blending of hydrogen with natural gas could provide a seamless transition and minimize disruptions in power and heating source distribution to the public. Academic institutions, industry, and governments globally, are supporting research, development and deployment of hydrogen blending projects such as HyDeploy, GRHYD, THyGA, HyBlend, and others which are all seeking to develop efficient pathways to meet the carbon reduction goal in coming decades. There is an understanding that successful commercialization of hydrogen blending requires both scientific advances and favorable techno-economic analysis. Ongoing studies are focused on understanding how the properties of methane-hydrogen mixtures such as density, viscosity, phase interactions, and energy densities impact large-scale transportation via pipeline networks and end-use applications such as in modified engines, oven burners, boilers, stoves, and fuel cells. The advantages of hydrogen as a non-carbon energy carrier need to be balanced with safety concerns of blended gas during transport, such as overpressure and leakage in pipelines. While studies on the short-term hydrogen embrittlement effect have shown essentially no degradation in the metal tensile strength of pipelines, the long-term hydrogen embrittlement effect on pipelines is still the focus of research in other studies. Furthermore, pressure reduction is one of the drawbacks that hydrogen blending brings to the cost dynamics of blended gas transport. Hence, techno-economic models are also being developed to understand the energy transportation efficiency and to estimate the true cost of delivery of hydrogen blended natural gas as we move to decarbonize our energy systems. This review captures key large-scale efforts around the world that are designed to increase the confidence for a global transition to methane-hydrogen gas blends as a precursor to the adoption of a hydrogen economy by 2050.